BEACH CLEANUP ACTION AS AN EFFORT TO IMPROVE ENVIRONMENTAL CLEANLINESS AT LOANG BALOQ BEACH, LOMBOK ISLAND, INDONESIA - Slamet Mardiyanto Rahayu; Novi Sri Rahmi; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Isti Dari Sofianti; Nurfaidah Nurfaidah; Syatriawan Perdana Putra; I Made Putu Sudiartha Hartawan; Amirudin Amirudin; Ni Made Ayu Tianyar (Nusantara Hasana Journal, 2026)
Lombok is one of the islands in the Lesser Sunda Islands group that offers various tourist attractions, one of which is Loang Baloq Beach. Community service activities carried out at Loang Baloq Beach in Mataram City demonstrated that a direct approach through beach cleanups and education has a positive impact on public and tourist awareness in maintaining a clean coastal environment. This method is effective in building public participation, increasing understanding, and encouraging collective behavioral change. Therefore, such activities need to be carried out regularly and continuously with the support of various parties, in order to establish a more participatory, educational, and sustainable coastal waste management system.